A report of the AGCPD task force to evaluate associations between select admissions requirements, demographics, and performance on ABGC certification examination. Issue 2 (2nd December 2021) - Myers, Melanie F.; Bergner, Amanda; Conway, Laura; Duquette, Debra; Durst, Andrea L.; Yashar, Beverly M.; Zhang, Xue; Campion, MaryAnn
Abstract: Graduation from a genetic counseling graduate program accredited by the Accreditation Council of Genetic Counseling and certification obtained by passing the American Board of Genetic Counseling (ABGC) certification examination are increasingly required to practice as a genetic counselor in the USA. Despite the ABGC certification examination serving as a gateway to the genetic counseling career, there have been no research studies to date that have examined what variables are associated with examination performance. Therefore, the Association of Genetic Counseling Program Directors established a Task Force to assess whether trainee demographics, Grade point average (GPA) and Graduate Record Exam (GRE®) percentile scores are associated with passing the ABGC certification examination on the first attempt. We surveyed accredited genetic counseling graduate programs in North America and gathered demographic data, admissions variables, and certification examination outcome data for 1, 494 trainees from 24 training programs, representing approximately 60.5% of matriculants between 2007 and 2016. Univariable analysis was performed to assess associations between admissions variables and categorical outcome (pass vs. fail) on the certification examination using Wilcoxon rank‐sum or Fisher's exact test. Variables significantly associated with the categorical board outcome were then entered in a stepwise model selection procedure. In stepwise logistic regression, trainees with higher GPA (OR = 3.41; 95% CI = 1.99, 5.83), higher verbal (OR = 1.02; 95% CI = 1.01, 1.03) and quantitative (OR = 1.02; 95% CI = 1.01, 1.03) GRE® scores, female trainees (OR = 2.95; 95% CI = 1.70, 5.12), and White trainees (OR 3.37; 95% CI = 2.14, 5.30) had higher odds of passing the certification examination on the first attempt. As programs move to a holistic approach to graduate admissions in order to improve access to the genetic counseling profession, our results may influence programs to provide additional preparation for the certification examination for all trainees. In addition, genetic counseling professional organizations should continue to work together to assess and eliminate outcome disparities in admissions, training, and certification processes.